2007
DOI: 10.1016/j.metabol.2006.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determination of adiponectin and its relationship with body fat topography in multigenerational families of African heritage

Abstract: Adiponectin, an adipose-specific protein, is negatively associated with adiposity, insulin sensitivity, and diabetes. Very few studies have examined the role of heredity in the regulation of adiponectin and its association with body fat among individuals of African heritage. Thus, we measured fasting serum adiponectin levels by radioimmunoassay and body composition by dual-energy x-ray absorptiometry (DEXA) in 402 individuals aged 18 to 103 years belonging to 7 multigenerational families of African heritage in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The heritability estimates of plasma adiponectin are high with roughly 50-60% (4,12-14). The ADIPOQ locus accounts for 6.7% of the variance in our populations-based KORA Study, which is in-line with previous reports (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heritability estimates of plasma adiponectin are high with roughly 50-60% (4,12-14). The ADIPOQ locus accounts for 6.7% of the variance in our populations-based KORA Study, which is in-line with previous reports (10).…”
Section: Discussionmentioning
confidence: 99%
“…An explanation for these differences is lacking as plasma adiponectin is only moderately influenced by nutritional behavior, physical activity or other environmental components (5,8,11). However, there is clear evidence for a high heritability of about 50% (4,12-14) which one study even suggested to be sex-dependent (14). In line with lower plasma adiponectin in men, higher prevalences of type 2 diabetes and impaired fasting glucose were also reported in men (15).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Crowther et al [48] have also shown that serum total adiponectin levels are lower in South African blacks when compared with South African whites. In this regard, recent studies in the West Indies showed that lower adiponectin has strong genetic inheritance among multiple generations of these populations [55]. These studies implicate alterations in proinflammatory markers and adipocytokines in the pathogenesis of CVD and type 2 diabetes in black PAD.…”
Section: Insulin Resistance and Inflammation In Black People Of The Amentioning
confidence: 92%
“…Several studies also showed that genetic loci (Menzaghi et al, 2007;Rankinen et al, 2006) other than LEP and APM1 genes were implicated to be linked to or associated with the circulating levels of leptin or adiponectin, and the main influences of these adipokine levels remain largely unknown. Previous studies in families reported significant genetic influences on the variation of the circulating levels of leptin (Bayoumi et al, 2007;Livshits et al, 2005) and adiponectin (Butte et al, 2005;Chuang et al, 2004;Comuzzie et al, 2001;Hicks et al, 2007;Lindsay et al, 2003;Miljkovic-Gacic et al, 2007). Nevertheless, heritability estimated from family studies might be confounded by the influences from shared environment and hence overestimate heritability.…”
mentioning
confidence: 99%